Fluid structure interaction simulation of left ventricular flow dynamics under left ventricular assist device support - Ong, C.W.; Chan, B.T.; Lim, E.; Abu Osman, Noor Azuan; Abed, A.A.; Dokos, S.; Lovell, N.H. (2012)
For patient’s receiving mechanical circulatory support, malfunction of the left ventricular assist device (LVADs) as well as mal-positioning of the cannula imposes serious threats to their life. It is therefore important to characterize the flow pattern and pressure distribution within the ventricle in the presence of an LVAD. In this paper, we present a 2D axisymmetric fluid structure interaction model of the passive left ventricle (LV) incorporating an LVAD cannula to simulate the effect of the LVAD cannula placement on the vortex dynamics. Results showed that larger recirculation area was formed at the cannula tip with increasing cannula insertion depth, and this is believed to reduce the risk of thrombus formation. Furthermore, we also simulated suction events (collapse of the LV) by closing the inlet. Vortex patterns were significantly altered under this condition, and the greatest LV wall displacement was observed at the part of the myocardium closest to the cannula tip